Associação entre tipos específicos de HPV e carga viral com a gravidade da neoplasia cervical - Guimarães, Narriman Kennia da Silva Barros (2012)
Introduction: Cervical cancer is a rare consequence and developed long term from a infection by specific types of human papillomavirus (HPV). There are factors related to the acquisition of infection and its persistence that increase the risk of developing cervical neoplasia. The type-specific viral infection and higher viral loads values appear to be related to persistence of virus and progression of neoplasia and therefore with the severity of cervical neoplasia. Objectives: To identify the specific types of HPV in different age groups as well as the importance of viral load of HPV 16 with the severity of cervical neoplasia. Methods: This cross-sectional study conducted in Goiânia, Goiás, included women referred to the Hospitals Santa Casa de Misericórdia de Goiânia and Hospital Mother and Child, by presenting changes in routine cytological examination. HPV DNA was detected by polymerase chain reaction (PCR) and HPV genotyping was performed by reverse hybridization assay. A total of 331 women with cytological diagnosis were selected, 238 of them with histological diagnosis. After PCR for HPV, 58 women were excluded for being HPV negative. In the 273 HPV-positive women an analysis of the association between HPV types and risk of severity of cytological diagnosis by age group was carried out in the following categorization: <30 years, 30-39 years, 40-49 years and ≥ 50 years. To evaluate the association between viral load values with severity of cytological and histological diagnosis, 77 women HPV 16 positive by PCR in real time were selected. Results: The overall prevalence of HPV infection was 82.5%. HPV 16 was the most prevalent type representing 44.7% of cases. Infections by HPV 16 and / or 18 were significantly associated with both the cytological diagnosis of HSIL or more severe lesions (OR: 2.12 95% CI 0.98 to 4.59) and either with the histological diagnosis of CIN 2 or more severe (OR: 3.21 95% CI 1.21 to 8.59) lesions in women younger than 30 years. The cytological diagnosis of HSIL or more severe lesions (OR 4.59, 95% CI: 1.4 to 15.49, p = 0.004) and histological diagnosis of high-grade neoplasia (≥ CIN 2) (OR 6.51; 95% CI: 2.9 to 20.92, p = 0.0002) were significantly associated with higher viral load values in women infected with HPV 16. Conclusions: These results support the hypothesis that infection with HPV 16 and / or 18 in young women can quickly lead to the formation of more severe lesions and high viral loads resulting from infection by HPV 16 are associated with the severity of cervical neoplasia.